GLP-1 RECEPTOR AGONISTS IN METABOLIC DYSFUNCTION-ASSOCIATED STEATOTIC LIVER DISEASE: THERAPEUTIC POTENTIAL AND CLINICAL CHALLENGES - Michał Bzoma; Hubert Bochenek; Paweł Kamiński; Irmina Czerepak; Julia Gugulska; Anna Bielicka; Tomasz Szwarc; Mateusz Kałwik; Karolina Niewczas; Adrianna Brzozowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), represents the most common chronic liver condition worldwide, strongly linked to obesity and type 2 diabetes. The more severe form, metabolic dysfunction-associated steatohepatitis (MASH), significantly increases risks of cirrhosis, hepatocellular carcinoma, and cardiovascular complications. Currently, effective pharmacological treatments are limited. This review aims to summarize current evidence on the potential role of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) as therapeutic agents for MASLD/MASH. Description of the State of Knowledge: GLP-1 RAs, currently used to treat diabetes and obesity, show beneficial metabolic effects through appetite reduction, weight loss, and improved glycemic control. Recent studies indicate that GLP-1 RAs, particularly liraglutide and semaglutide, effectively reduce liver steatosis, hepatic inflammation, and liver enzymes. However, evidence regarding their effectiveness in reducing liver fibrosis remains unclear, highlighting the need for larger and longer studies. Conclusions: GLP-1 RAs emerge as promising therapeutic options for MASLD and MASH due to their metabolic and hepatoprotective benefits. While preliminary findings support their use, particularly in reducing hepatic steatosis and inflammation, their role in fibrosis regression requires further validation. Future research, involving extensive clinical trials with broader patient populations and standardized dosing protocols, is essential to establish GLP-1 RAs as standard therapy for metabolic liver disease.